Peripapillary hyper-reflective ovoid mass-like structures (PHOMS): clinical significance, associations, and prognostic implications in ophthalmic conditions - Li, Biao; Li, Haoran; Huang, Qun; Zheng, Yanlin (Frontiers in Neurology, 2023)
Pioneering advancements in optical coherence tomography (OCT) have facilitated the discernment of peripapillary hyper-reflective ovoid mass-like structures (PHOMS), prevalent neuro-ophthalmological findings associated with an array of ophthalmic conditions, such as optic disc drusen (ODD), papilledema, myopic/tilted optic discs, non-arteritic anterior ischemic optic neuropathy (NA-AION), and optic neuritis. Despite an expanding corpus of research, numerous inquiries persist concerning their clinical significance, correlations with ocular afflictions, and prognostic implications. This comprehensive review endeavors to impart an in-depth comprehension of PHOMS, encompassing facets like conceptualization, detection, pathogenesis, and associations with diverse ophthalmic conditions. Furthermore, we underscore several unresolved quandaries and suggest prospective avenues for future exploration.